CNR considerations for rapid real‐time MRI tumor tracking in radiotherapy hybrid devices: Effects of B0 field strength. Issue 8 (1st August 2016) - Wachowicz, K.; De Zanche, N.; Yip, E.; Volotovskyy, V.; Fallone, B. G.
Abstract : Purpose: This work examines the subject of contrast‐to‐noise ratio (CNR), specifically between tumor and tissue background, and its dependence on the MRI field strength, B 0 . This examination is motivated by the recent interest and developments in MRI/radiotherapy hybrids where real‐time imaging can be used to guide treatment beams. The ability to distinguish a tumor from background tissue is of primary importance in this field, and this work seeks to elucidate the complex relationship between the CNR and B 0 that is too often assumed to be purely linear. Methods: Experimentally based models of B 0 ‐dependant relaxation for various tumor and normal tissues from the literature were used in conjunction with signal equations for MR sequences suitable for rapid real‐time imaging to develop field‐dependent predictions for CNR. These CNR models were developed for liver, lung, breast, glioma, and kidney tumors for spoiled gradient‐echo, balanced steady‐state free precession (bSSFP), and single‐shot half‐Fourier fast spin echo sequences. Results: Due to the pattern in which the relaxation properties of tissues are found to vary over B 0 field (specifically the T 1 time), there was always an improved CNR at lower fields compared to linear dependency. Further, in some tumor sites, the CNR at lower fields was found to be comparable to, or sometimes higher than those at higher fields (i.e., bSSFP CNR for glioma, kidney, and liver tumors). Conclusions: In terms of CNR, lower B 0 fields have been shown to perform as well or better than higher fields for some tumor sites due to superior T 1 contrast. In other sites this effect was less pronounced, reversing the CNR advantage. This complex relationship between CNR and B 0 reveals both low and high magnetic fields as viable options for tumor tracking in MRI/radiotherapy hybrids.